Optical coherence tomography guided retreatment of photodynamic therapy. Issue 9 (19th August 2005) - Krebs, I; Binder, S; Stolba, U; Schmid, K; Glittenberg, C; Brannath, W; Goll, A
Abstract : Aim: To evaluate the results of a retreatment modality of photodynamic therapy (PDT) based on optical coherence tomography (OCT) and fluorescein angiography (FA). To quantify the effect of PDT with the help of measurement of the retinal thickness. Methods: Eyes with predominantly classic subfoveal choroidal neovascularisation (CNV) due to age related macular degeneration were included. PDT was performed every three months, when needed. OCT, FA, and measures of distance acuity were performed at baseline, after 6 weeks, 3 months, and from then on every 3 months. A control group of a consecutive series of eyes that had been retreated based only on FA results was installed. Results: Forty eyes of 38 patients were included. The average age was 73 years. The maximum retinal thickness decreased from 404 μm at baseline to 281.6 μm at month 12. Furthermore there was a significant decrease of retinal thickness in both subgroups. The number of retreatments was reduced, when activity was diagnosed using OCT and FA. (2.4 v 4.0). The distance acuity correlated significantly with the maximum retinal thickness (p = 0.0042). Conclusion: Information about the activity of a neovascular lesion can be obtained with the help of OCT. The retreatment modalities can be optimised by using OCT and FA and the number of retreatments can be reduced.